1991
DOI: 10.1139/o91-011
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of ribonucleotide reductases by peptides corresponding to the C-terminal of their second subunit

Abstract: Previous studies have shown that herpes virus ribonucleotide reductase can be inhibited by a synthetic nonapeptide whose sequence is identical to the C-terminal of the small subunit of the enzyme. This peptide is able to interfere with normal subunit association that takes place through the C-terminal of the small subunit. In this report, we illustrate that inhibition of ribonucleotide reductases by peptides corresponding to the C-terminal of subunit R2 is also observed for the enzyme isolated from Escherichia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…This part of R2 has an important role in the association with the R1 protein [2][3][4][5][6][7][8][9]. The NMR observable segment also contains the conserved residues, Tyr-356 and Glu-350, that are invariable between species [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This part of R2 has an important role in the association with the R1 protein [2][3][4][5][6][7][8][9]. The NMR observable segment also contains the conserved residues, Tyr-356 and Glu-350, that are invariable between species [22].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the carboxyl terminal part of protein R2 is important for the binding of protein R2 to protein R1 both in the E. eoli enzyme [24] and in the mammalian and Herpes simplex type I enzymes [5][6][7][8][9]. Truncations of C-terminal residues of protein R2 impair binding of protein R1 [2], and point mutations of conserved residues in the C-terminus reduces or abolishes catalytic activity [34].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it does not seem to be essential for catalytic activity (39). The C-terminal seven residues, which were shown to be essential for binding between the R1 and R2 proteins in the mouse RNR (35,36), show high similarity between the trypanosome and mouse R2 proteins. The only difference is that Thr-385 (mouse R2 numbering) is replaced by a serine in the T. brucei R2 protein.…”
Section: Cloning and Sequencing Of T Brucei R1 And R2 Cdnasmentioning
confidence: 99%
“…This observation led to the develop-ment of potent peptidomimetic inhibitors of HSV RNR with antiviral activity in vivo (34). The inhibitory effect of R2 C-terminal peptides has also been demonstrated for mammalian (35,36) and E. coli class Ia (37) RNRs.…”
mentioning
confidence: 99%
“…In mouse R2, the C-terminal 7 residues are essential for subunit interactions while the C-terminal peptide with the same function in E. coli R2 is much longer [18]. The mouse C-terminal heptapeptide was shown to be highly flexible and unstructured by NMR studies, but on addition of R1 it becomes rigid and structured [19].…”
Section: Introductionmentioning
confidence: 99%